PENGARUH PENGGUNAAN MEDIA PAPAN DIAGRAM TERHADAP HASIL BELAJAR MATERI STATISTIKA SISWA SEKOLAH DASAR - Ratnasari, Anak Agung Ketut dewi; Kertayasa, I Ketut; Narayanti, Putu Satya (JATMIKA : Journal Education and Learning of Elementary School, 2024)
The aim of this research was to determine the effect of using diagram board media on the learning outcomes of statistics material for fourth grade students at SD Inpres Tipo and to find out students' responses to the use of diagram board media in statistics material. The sampling technique is non-probability sampling with a sample size of 30 students. The instruments used in this research were multiple choice questions and student response questionnaires, and were validated by validating content, language and constructs as well as documentation. The method used is quantitative with a pre-experimental design research type with data analysis techniques used, namely normality and homogeneity tests of questions and hypothesis testing. The research results obtained show that learning before using diagram board media obtained an average learning outcome of 58.33% and learning after using diagram board media obtained an average learning outcome of 76.33% and the average difference was 18% with tcount is 8.464 and ttable is 1.699, so tcount is > from ttable so that ho is rejected and h1 is accepted, so there is an influence of the use of diagram board media on learning outcomes in statistics material in class IV SD Inpres Tipo. Based on the questionnaire, students obtained a good category with a score of 79.6.